Hypertext as a Form of Artistic Refl ection of Reality in the Digitalization Era - Ksenia V. Zeynalova; Igor A. Romanov (Гуманитарный вектор)
The article considers hypertext as a form of artistic refl ection of reality that emerged at the end of the twentieth century, where individualization and computer technologies come to the fore. Initially, the concept of “hypertext” was used in the fi eld of programming. However, the concept of “branching” turned out to be promising, and researchers started talking about hypertext literature. In this regard, the purpose of the study is to consider hypertext as a form of artistic refl ection of reality in the era of digitalization. The article uses the following literary methods: cultural-historical, phenomenological, the method of structural analysis of the text. The scientifi c novelty of the research is determined by the need to determine the patterns of development of hypertext literature and to identify its specifi cs. The article reveals the main features of literary hypertext: non-linearity, fragmentation, multi-authorship, interactivity. In addition, we can see how the form of interaction with the text is changing: there is no traditional paradigm of “author – text – reader” in front of us. Bakhtin’s concept of dialogue is replaced by R. Barth’s idea of the author’s death. Hypertext literature builds a new way of interacting with the text, in which the reader takes the place of the author. The theoretical provisions of the work were confi rmed by the analysis and evaluation of foreign and Russian hypernovels. The article also suggests that the main reason for the collapse of the traditional linear narrative in literature is social atomization, which inevitably leads to the disappearance of genuine dialogue in the modern world. The results of the study can be used in the study of the culture of the era of digitalization. In addition, the identifi cation of examples of genuine dialogism associated with the reader’s understanding of the author’s idea in the works of electronic hypertext literature, intertextual references to other texts as a way of semantic increment and not the implementation of a purely game strategy seems quite promising for the complex of sciences involved in the identifi cation of meanings in modern culture: philosophy, literary studies, semiotics, cultural studies.